Nematic suspension of a microporous layered silicate obtained by forceless spontaneous delamination via repulsive osmotic swelling for casting high-barrier all-inorganic films - Loch, Patrick; Schuchardt, Dominik; Algara-Siller, Gerardo; Markus, Paul; Ottermann, Katharina; Rosenfeldt, Sabine; Lunkenbein, Thomas; Schwieger, Wilhelm; Papastavrou, Georg; Breu, Josef (Science Advances, 2022)
Exploiting the full potential of layered materials for a broad range of applications requires delamination into functional nanosheets. Delamination via repulsive osmotic swelling is driven by thermodynamics and represents the most gentle route to obtain nematic liquid crystals consisting exclusively of single-layer nanosheets. This mechanism was, however, long limited to very few compounds, including 2:1-type clay minerals, layered titanates, or niobates. Despite the great potential of zeolites and their microporous layered counterparts, nanosheet production is challenging and troublesome, and published procedures implied the use of some shearing forces. Here, we present a scalable, eco-friendly, and utter delamination of the microporous layered silicate ilerite into single-layer nanosheets that extends repulsive delamination to the class of layered zeolites. As the sheet diameter is preserved, nematic suspensions with cofacial nanosheets of ≈9000 aspect ratio are obtained that can be cast into oriented films, e.g., for barrier applications.
CRIS-Team Scopus Importer:2022-06-03